Archives and Records Privacy, Personality Rights, and Access - Čtvrtník, Mikuláš (Springer Nature, 2023)
This open access book addresses the protection of privacy and personality rights in public records, records management, historical sources, and archives; and historical and current access to them in a broad international comparative perspective. Considering the question "can archiving pose a security risk to the protection of sensitive data and human rights?", it analyses data security and presents several significant cases of the misuse of sensitive personal data, such as census data or medical records. It examines archival inflation and the minimisation and reduction of data in public records and archives, including data anonymisation and pseudonymisation, and the risks of deanonymisation and reidentification of persons. The book looks at post-mortem privacy protection, the relationship of the right to know and the right to be forgotten and introduces a specific model of four categories of the right to be forgotten. In its conclusion, the book presents a set of recommendations for archives and records management.